Participatory diagnosis and development of climate change adaptive capacity in the groundnut basin of Senegal: building a climate-smart village model - Sanogo, Diaminatou; Ndour, Yacine; Sall, Moussa; Touré, Katim; Diop, Mouhamadou; Camara, Baba Ansoumana; Ndiaye, Ousmane; Thiam, Djibril (Springer, 2017)
Background: Up to now, efforts to help local communities out of the food-insecurity trap were guided by researcher (or other actors)-led decisions on technologies to be implemented by the communities. This approach has proved inefficient because of low adoption of the so-called improved technologies. This paper describes the strategic approaches to the development of a climate-smart village (CSV) model in the groundnut basin of Senegal. A CSV model is a participatory integrated approach using climate information, improved context-based technologies/practices aiming at reaching improved productivity (food and nutrition security), climate resilient people and ecosystem and climate mitigation. In this study, participatory vulnerability analysis, planning adaptation capacity and participatory communication for development were implemented, putting people affected by the impacts of climate change (CC) at the center of the approach. Four interdependent groups of activities/domains, namely—local and institutional knowledge, use of climate information services, development of climate-smart technology and local development plans, were covered. It was emphasized, how all this taken together could create improved livelihoods for women, men and vulnerable groups.